Analysis of Student Progress in Mathematics Learning at Vocational High Schools to Support the Strengthening of SDGs’ - Utami, Wikan Budi; Fayeldi, Trija; Vaz, Benjamin Laurentino (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
Student development is a multidimensional cornerstone of vocational education that determines learning effectiveness, yet it is often analyzed through a purely cognitive lens. This study aims to analyze the multidimensional development of students encompassing physical-psychomotor, cognitive, and emotional dimensions and identify the factors influencing their success and difficulties in mathematics learning. Using a descriptive qualitative approach under an interpretivist paradigm, the research focused on three eleventh-grade students at a private Vocational High School (SMK) in Malang, selected through purposive sampling. Data were collected over four weeks through direct observation, semi structured interviews, and diagnostic questionnaires, followed by thematic content analysis using the Miles and Huberman model. The results reveal three distinct developmental profiles, namely subject P1 demonstrates high emotional resilience and stable motor coordination, which facilitates independent problem-solving; subject P2 exhibits significant academic anxiety and motor hesitation, leading to a dependency on concrete scaffolding; and subject P3 shows systematic reasoning supported by strong visual-motor strategies. The study identifies intrinsic motivation and tool proficiency as key supporting factors, while evaluation anxiety and abstract-conceptual gaps act as primary inhibitors. These findings provide a holistic profile of vocational students and offer strategic recommendations for teachers to design inclusive, kinesthetic-based learning. This research directly supports the strengthening of SDG 4 (Quality Education), SDG 3 (Good Health and Well-Being), and SDG 10 (Reduced Inequalities) by advocating for a more humane and adaptive mathematics education framework. Abstrak: Perkembangan siswa merupakan landasan multidimensi dalam pendidikan vokasi yang menentukan efektivitas pembelajaran, namun seringkali hanya dianalisis melalui lensa kognitif semata. Penelitian ini bertujuan untuk menganalisis perkembangan multidimensi siswa yang mencakup dimensi fisik psikomotorik, kognitif, dan emosional serta mengidentifikasi faktor-faktor yang memengaruhi keberhasilan dan kesulitan mereka dalam pembelajaran matematika. Menggunakan pendekatan kualitatif deskriptif di bawah paradigma interpretivisme, penelitian ini berfokus pada tiga siswa kelas sebelas di sebuah Sekolah Menengah Kejuruan (SMK) swasta di Malang, yang dipilih melalui purposive sampling. Data dikumpulkan selama empat minggu melalui observasi langsung, wawancara semi-terstruktur, dan kuesioner diagnostik, yang dilanjutkan dengan analisis isi tematik menggunakan model Miles dan Huberman. Hasil penelitian mengungkapkan tiga profil perkembangan yang berbeda: (1) Subjek P1 menunjukkan resiliensi emosional yang tinggi dan koordinasi motorik yang stabil, yang memfasilitasi pemecahan masalah secara mandiri; (2) Subjek P2 menunjukkan kecemasan akademik dan keraguan motorik yang signifikan, sehingga menyebabkan ketergantungan pada perancah (scaffnelitian ini secarolding) konkret; dan (3) Subjek P3 menunjukkan penalaran sistematis yang didukung oleh strategi visual-motorik yang kuat. Penelitian ini mengidentifikasi motivasi intrinsik dan kemahiran penggunaan alat bantu sebagai faktor pendukung utama, sementara kecemasan terhadap evaluasi dan kesenjangan konsep abstrak bertindak sebagai penghambat utama. Temuan ini menyajikan profil holistik siswa vokasi dan menawarkan rekomendasi strategis bagi guru untuk merancang pembelajaran berbasis kinestetik yang inklusif. Pea langsung mendukung penguatan SDG 4 (Pendidikan Berkualitas), SDG 3 (Kehidupan Sehat dan Sejahtera), dan SDG 10 (Berkurangnya Kesenjangan) dengan mengadvokasi kerangka kerja pendidikan matematika yang lebih manusiawi dan adaptif.